Evaluation of the Inclusion of the Seaweed Ulva lactuca Produced in an Integrated System with Biofloc in the Diet of Juvenile Tilapia Oreochromis niloticus - Andrezza Carvalho; Larissa Müller; Victor Rosas; Marcelo Borges Tesser; Juliane Ventura-Lima; Gamze Turan; Marcelo Pias; Luís H. Poersch (Applied Sciences, 2025)
Macroalgae biomass produced in integrated biofloc systems can become a high-quality nutritional product to replace ingredients in the diet of tilapia. This study aimed to evaluate the effects of different concentrations of Ulva lactuca on the performance and antioxidant capacity of Nile tilapia. There were four isoprotein and isolipid diets with 5%, 10%, and 15% macroalgae meal, and a control treatment without macroalgae inclusion. The experiment lasted for 42 days in a recirculating system, with animal performance, blood sampling, and proximal composition being carried out. To assess the potential benefits of including algal biomass, a salinity stress test was carried out on the fish, and samples were collected for biochemical analysis. There were no significant differences in carcass performance and composition between the treatments. The results showed that the inclusion of 10% macroalgae resulted in a higher granulocyte count, while the antioxidant capacity obtained better results in the 5 and 10% macroalgae inclusions, followed by the modulation of the antioxidant system, as evidenced by an increase in glutathione-S-transferase activity and reduced glutathione levels. However, protein and lipid oxidation did not occur only in the 5% macroalgae inclusion compared with the treatments with higher algae inclusion. Therefore, the inclusion of 5% macroalgae in the tilapia diet is indicated to improve antioxidant capacity in the face of stress.